PsycEXTRA Dataset 2003
DOI: 10.1037/e615452012-003
|View full text |Cite
|
Sign up to set email alerts
|

Multiple roles and women's mental health in Canada

Abstract: Health Issue: Research on the relationship between women's social roles and mental health has been equivocal. Although a greater number of roles often protect mental health, certain combinations can lead to strain. Our study explored the moderating affects of different role combinations on women's mental health by examining associations with socioeconomic status and differences in women's distress (depressive symptoms, personal stress (role strain) and chronic stress (role strain plus environmental stressors).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…This could be described as an everyday pattern, with a lack of meaningful engagement in occupations, combined with environmental demands (e.g. motherhood) or disturbances, leading to dissatisfaction or, with reference to other studies (14,37), to stress and lower self-reported health. In our study, problematic alcohol consumption was not associated with living under strained or disadvantaged life circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…This could be described as an everyday pattern, with a lack of meaningful engagement in occupations, combined with environmental demands (e.g. motherhood) or disturbances, leading to dissatisfaction or, with reference to other studies (14,37), to stress and lower self-reported health. In our study, problematic alcohol consumption was not associated with living under strained or disadvantaged life circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…In Canada and other industrial nations, differential exposures to workplace stressors are partially explained by an unequal sex distribution among occupations that generally render women of diverse ages and social strata (Maclean et al, 2004) more vulnerable to adverse D-C-S profiles and associated psychiatric symptoms (Marchand et al, 2005a,b,c;Vermeulen & Mustard, 2000). For example, women have a higher lifetime risk of developing depressive and anxiety disorders than do men (Seedat et al, 2009).…”
Section: Introductionmentioning
confidence: 97%
“…In Canada and other industrial nations, differential exposures to workplace stressors are partially explained by an unequal sex distribution among occupations that often render women of diverse ages and social strata 128 more vulnerable to psychiatric disorders. 129 -131 These sex differences may be due, in part, to divergent gender roles and ranks held within occupational hierarchies.…”
Section: Gender Diversity In Almentioning
confidence: 99%